The construct validity of the main student selection tests for medical studies in Germany - Levacher, Julie; Koch, Marco; Stegt, Stephan J.; Hissbach, Johanna; Spinath, Frank M.; Escher, Malvin; Becker, Nicolas (Frontiers in Education, 2023)
Standardised ability tests that are associated with intelligence are often used for student selection. In Germany two different admission procedures to select students for medical studies are used simultaneously; the TMS and the HAM-Nat. Due to this simultaneous use of both a detailed analysis of the construct validity is mandatory. Therefore, the aim of the study is the construct validation of both selection procedures by using data of 4,528 participants (Mage = 20.42, SD = 2.74) who took part in a preparation study under low stakes conditions. This study compares different model specifications within the correlational structure of intelligence factors as well as analysis the g-factor consistency of the admission tests. Results reveal that all subtests are correlated substantially. Furthermore, confirmatory factor analyses demonstrate that both admission tests (and their subtests) are related to g as well as to a further test-specific-factor. Therefore, from a psychometric point of view, the simultaneous use of both student selection procedures appears to be legitimate.